2016
DOI: 10.5807/kjohn.2016.25.2.96
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Shift Work and Hours of Sleep on Metabolic Syndrome in Korean Workers

Abstract: The purpose of this study was to investigate the effects of shift work and hours of sleep on metabolic syndrome in Korean workers. Methods: This study used the Korean National Health and Nutrition Examination Survey data of 2014. The study included 1,579 Korean workers aged over 20. x 2 test, t-test, and hierarchical multiple logistic regression were used for statistical analysis of data. Results: From the univariate analysis, hours of sleep, regular work, occupational group, sex, age, marital status, educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In Korea, males tend to dominate shift work and manual labor 32,33 , both of which were found to be associated with poorer adherence to medications in our study. With this in consideration, we conducted gender-stratified analyses to examine the interactions between gender and each variable as well as the association between poor medication adherence and work schedules (Supplementary Table 2, 3).…”
Section: Discussionmentioning
confidence: 52%
“…In Korea, males tend to dominate shift work and manual labor 32,33 , both of which were found to be associated with poorer adherence to medications in our study. With this in consideration, we conducted gender-stratified analyses to examine the interactions between gender and each variable as well as the association between poor medication adherence and work schedules (Supplementary Table 2, 3).…”
Section: Discussionmentioning
confidence: 52%
“…Participants working nonregular shifts showed a higher incidence of symptoms of depression. Previous studies have reported that nonregular shifts may cause physical and mental health issues [ 39 , 40 , 41 , 42 , 43 ]. In one study, rotating shift was found to be five times more likely to cause shift work sleep disorder than regular shift, and individuals with shift work sleep disorder reported an increase in the levels of depression and anxiety symptoms [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, there is a trend in South Korea of reducing sleep time to allow for incorporating various tasks into the day, which is detrimental to health and fitness. The number of South Korean adults with short sleep durations is increasing, and individuals with daily sleep durations of less than 6 hours are at a higher risk for metabolic syndrome than those with more than 6 hours (Kim, 2018; Park, 2016). Furthermore, people with short sleep durations appear to exhibit higher chronic psychological stress (Glozier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%